Detection of Adulteration of Panax Notoginseng Powder by Terahertz Technology - Li, Bin; Yin, Hai; Yang, A-kun; Ouyang, Ai-guo (Journal of Spectroscopy, 2022)
The combined terahertz time-domain spectroscopy (THz-TDS) and chemometric technology is used to detect the adulteration of similar substances in Panax notoginseng powder. Four kinds of samples are prepared in the experiment, three kinds of adulterated samples are Panax notoginseng powder adulterating with zedoary turmeric powder, Panax notoginseng powder adulterating with wheat flour, and Panax notoginseng powder adulterating with rice flour, respectively. The values of adulterated concentration are from 5% to 60%, the interval of adulterated concentration is 5%, and the other sample is pure Panax notoginseng powder. The modeling and prediction sets are divided by 3 : 1 by class. The feature information of models is extracted by elimination of uninformative variable (UVE) method and successive projection algorithm (SPA); combining with back propagation neural network (BPNN), the UVE-BPNN and SPA-BPNN qualitative models are established, respectively. The model’s results show that the UVE-BPNN model is better; the classification accuracy of the prediction set of UVE-BPNN is 95%. Then, the least square support vector machine (LS-SVM) algorithm and partial least square (PLS) algorithm are used to establish the quantitative analysis model. The model’s results show that the LS-SVM model is better among the quantitative analysis models of zedoary turmeric powder and wheat flour, the correlation coefficient of prediction (RP) is 0.90 and 0.93 of LS-SVM, respectively, and the root mean square error of prediction (RMSEP) of LS-SVM is 0.072 and 0.068, respectively. Among the quantitative analysis models for rice noodles, the PLS model is better, with the RP of 0.94 and RMSEP of 0.06. The results show that the combined THz-TDS and chemometric technology can be used to determine the adulteration of similar substances in Panax notoginseng powder quickly, accurately, and nondestructively.